Os caminhos da docência na era digital: a utilização da sala de informática em escolas de São Carlos - Medeiros, Lilian Maria de (Universidade Federal de São Carlos, 2008)
In the present context, the continuous technological innovations and the emergence of new technologies allow the increase of the communication possibilities and the exchange of information and knowledge between people. In the educational field, we have contributions from recent studies with respect to the use of computers by teachers in the school context and its implications, as the studies by Valente, Barreto, Kenski, Beloni, Borba and Penteado, Fernandes, Monaco, and others. The present work is related to this field and seeks to answer the following question: What do the teachers think about the computer classrooms of the project School of the Future in São Carlos city for the students teaching and learning process? The goal of this work was to identify and to analyze the conceptions about the utilization of computers for the teaching-learning process in the school units where the project School of the Future is taking place. The main data source of this work was the answers to the questionnaire and interviews given by teachers who work in the school units where the project has been implemented. I analyzed the teachers perceptions on the possible contributions of the TICs to the work that has been carried out in the schools; on the students reactions to the use of computers in the classrooms; on the project School of the Future ; on the rules related to the use of the computer classrooms; and on the educational requirements for using the computers as a pedagogical tool. I used a questionnaire with open and close questions and semi-structured interviews in order to collect the data, which was analyzed later on in a qualitative way with the aim of establishing relations and identifying the perspectives of the research volunteers. For organization and systematization, some data is presented in graphs. To conclude, I realized that the teachers who took part in this research believe in the positive contribution of the use of computers in the school context, but they don t really use the available computers in the school due to lack of time, lack of skills or bureaucratic barriers. Also, many of them aren t aware of the school rules concerning the use of the computers, and in other cases, they believe that the computers classrooms should not be used by them. The data also revealed the necessity of some changes in the schools so that the teachers can use the available TICs, as well as more incentives by the education managers and the implementation of public policies for this practice.
Keywords: Informática na educação; Educação; Professores - formação; Novas tecnologias da comunicação; Education; Teacher education; New technologies of information and communication; CIENCIAS HUMANAS::EDUCACAO